Overcoming the Global Economic Crisis in The Perspective of Islamic Finance - Muhammad Rafi Siregar; Ahmad Rifai; Mariana Mariana (Al-Kharaj: Journal of Islamic Economic and Business, 2023)
This paper makes a connection between the global financial crisis and an Islamic financial model. The goal is to downplay the severity and frequency of the financial crisis by sharing risk among financial participants. This is accomplished through a system of shared credit creation. When purchasing real goods and services from people who have them and need to sell, people are given access to credit that they can use to buy what they need. Both sellers and buyers want to receive delivery of their purchased items, so the system creates economic growth through increased credit availability. Studying Islamic finance literature allows people to explore the possibilities and restrictions of inherited situations. This leads to new financial design solutions for the current financial crisis as well as future financial collapses. It also uses critical thinking and analysis to create new possibilities and constraints in situations. New financial systems should use a business model based on shared profits and losses. This was based on academic studies and doesn’t include any real-world testing. By incorporating Islamic financial principles into business practices, a new financial model could help finance businesses. This alternate system for the banking system could help control our financial system and encourage economic growth through more controlled credit expansion  TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//   This page is in English Translate to Indonesian    AfrikaansAlbanianAmharicArabicArmenianAzerbaijaniBengaliBulgarianCatalanCroatianCzechDanishDutchEnglishEstonianFinnishFrenchGermanGreekGujaratiHaitian CreoleHebrewHindiHungarianIcelandicIndonesianItalianJapaneseKannadaKazakhKhmerKoreanKurdish (Kurmanji)LaoLatvianLithuanianMalagasyMalayMalayalamMalteseMaoriMarathiMyanmar (Burmese)NepaliNorwegianPashtoPersianPolishPortuguesePunjabiRomanianRussianSamoanSimplified ChineseSlovakSlovenianSpanishSwedishTamilTeluguThaiTraditional ChineseTurkishUkrainianUrduVietnameseWelsh Always translate English to IndonesianPRO Never translate English Never translate ejournal.iainpalopo.ac.id